Analisis Strategi Pemulihan Citra Bank Syariah Indonesia Pasca Dugaan Serangan Siber - Maulana, Bagus Restu; Nasrulloh, Nasrulloh (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2024)
Indications of a cyberattack on Bank Syariah Indonesia (BSI) on May 8, 2023, led to a crisis of trust and a negative image. This study examines BSI image recovery strategy following the cyberattack. The research was conducted at BSI Branch Office in Jombang using a descriptive qualitative methodology, involving employees and customers as subjects. This study examines the strategy employed to rebuild customer trust and restore the tarnished image. This study employed the situational crisis communication theory (SCCT) and William L. Benoit's image recovery theory as analytical frameworks to examine BSI communication response and subsequent image recovery strategy. The findings revealed that BSI implemented responsive communication and crisis management strategies aligned with SCCT, in addition to image recovery initiatives that aimed to enhance positive perceptions and diminish negative sentiments, in accordance with Benoit's image recovery theory. These measures include BCP implementation, a gift party program, security enhancements, and weekend banking services. BSI demonstrated a commitment to improving its image and rebuilding customer trust through effective communication strategies. However, improvements are necessary in security planning and communication during a crisis to address customer concerns more effectively.